Just Married - Levy, Shawn; Murphy, Brittany, 1977-; Christian Kane; David Moscow; David Rasche; Monet Mazur; Thad Luckinbill; Ashton Kutcher (USA, Germany Mediastream Dritte Film GmbH & Co. Beteiligungs KG, 2003)
A happy young couple, Sarah and Tom (Brittany Murphy and Ashton Kutcher) marry against the wishes of Sarah's friends and family and go to Europe for their Honeymoon. Unfortunately for them, Sarah's parents send Sarah's ex-boyfriend Peter Prentis (played by Christian Kane) to break up the happy marriage.
A young newlywed couple honeymoon in Europe, where obstacles challenge their ability to sustain the marriage.
Sam Harper
Languages: English, Polish Subtitles: English, Turkish, Polish, Czech, Hungarian
Keywords: Romance; Comedy